Genetics, Family Structure, and Economic Growth - Paul J. Zak (Claremont McKenna College, Department of Economics, 2000)
Recent biomedical research shows that roughly three-quarters of cognitive abilities are attributable to genetics and family environment. This paper presents a theory of growth in which human capital is determined by inheritable factors and family size. The distribution of income is shown to affect the number of births, with greater inequality raising the fertility rates and reducing output growth in the transitional dynamics. If human or physical stocks are sufficiently low, the model shows that an economy can be caught in a fertility-caused poverty trap, while countries with more resources will converge to a balanced growth path where the average transmission of human capital from parents to childern determines the long-run rate of output growth.
Keywords: D9; J13; 330; genetics; siblings; growth; fertility; human capital